The Impact of Family Conflict on The Treatment of Students in Bullying in High Schools - Irwan Djumat; Nani I. Rajaloa; Balqis Nurmauli Damanik; Komari (Universitas Pendidikan Ganesha, 2024)
The problem of bullying is a phenomenon that often occurs in the school environment. Facts show that students who often commit bullying acts have a less harmonious family background. The aim of this study was to identify the relationship between family conflict and the stages of bullying in male students in secondary school. This type of research is quantitative research. The subjects were students whose population was 450 people and only 76 students had bullying tendencies. These 76 students were selected as a sample in the study. Data collection techniques with instruments. Question instrument to investigate the Stage of Bullying Behavior. Family Conflict Violence Investigation is used to measure the stages of student family conflict. Measurement with Likert scale 1-5. Descriptive statistical analysis techniques and inference statistics (Pearson correlation test). Results and findings show that bullying rates among male students tend to be at low levels (2.52). It was found that the frequency of conflict was minimal for the type of sibling conflict within the scope of students at school and the most frequent conflict between parents and students. The findings suggest that family conflict factors need serious attention and are taken into account in designing intervention programs to prevent the phenomenon of bullying from becoming more serious in schools. The implications of this study point to the need for serious attention to family conflict factors in designing intervention programs to prevent the phenomenon of bullying from becoming more serious in schools.